A blow-up criterion for the inhomogeneous incompressible Euler equations. (July 2020) - Bae, Hantaek; Lee, Woojae; Shin, Jaeyong
Abstract: In this paper, we first show the existence of local-in-time solutions the inhomogeneous incompressible Euler equations in R 3 . We then derive a refined blow-up criterion of these solutions.